Differential H3K9me2 heterochromatin levels and concordant mRNA expression in postmortem brain tissue of individuals with schizophrenia, bipolar, and controls - Rizavi, Hooriyah S.; Chase, Kayla A.; Liu, Chunyu; Gavin, Hannah; Rosen, Cherise; Xia, Cuihua; Guidotti, Alessandro; Sharma, Rajiv P. (Frontiers in Psychiatry, 2022)
The existence of repressive and durable chromatin assemblies along gene promoters or networks, especially in the brain, is of theoretical and therapeutic relevance in a subset of individuals diagnosed with schizophrenia who experience a chronic, persistent, and treatment-resistant trajectory. We used chromatin immunoprecipitation followed by deep sequencing (ChIP-Seq) to generate an epigenomic map that includes differential sites occupied by di-methylated lysine 9 of histone 3 (H3K9me2), a repressive modification that is yet unexplored in human postmortem brain tissue. We have discovered over 150 significantly differential promoter sites in the postmortem prefrontal cortex tissue of individuals diagnosed with schizophrenia (n=15) when compared to controls (n=15). Potentially dysregulated gene categories include postsynaptic proteins, processing enzymes (for proproteins, lipids, and oxidative stress), cadherin family genes, the complement system, and peptide hormones. Ten genes with significantly increased or decreased H3K9me2 promoter occupation were selected through statistical analysis, function, or previous GWAS association, and qRT-PCR was performed on an extended sample of postmortem brain tissue, adding an additional 17 controls, 7 individuals with schizophrenia, and 19 individuals with bipolar samples (n=32 control, 22 schizophrenia, 19 bipolar). This approach revealed that mRNA expression levels correlated with chromatin modification levels in eight of ten selected genes, and mRNA expression in the total sample could be predicted by the occupancy of H3K9me2. Utilization of this method and replication in a larger sample open a pathway to durable and restrictive epigenomic assemblies whose accumulation across the lifespan of individuals diagnosed with schizophrenia may explain treatment resistance and advance therapeutic options.